Pemanfaatan Koleksi Internasional Pada Layanan Mancanegara Perpustakaan Nasional Republik Indonesia - Johan, Yelen Deni Sari; Fransiska Timoria Samosir; Lailatus Sa’diyah (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2025)
This study aims to determine the utilization of international collections in the National Library's International Service. Using qualitative descriptive methods, data collection with data analysis techniques using the Miles & Huberman model, namely by using the techniques: data reduction, data presentation, and drawing conclusions. The results of the study indicate that this collection is in great demand, especially by students, due to a number of obstacles faced by users, such as language barriers and limited collections. Further analysis shows that internal factors such as user needs, interests, and motives, as well as external factors such as the completeness of the collection and librarian skills. Overall, international collections have great potential to support the development of science, but further efforts are needed to overcome obstacles and increase socialization. The results of the study show that this collection is in great demand, especially among students. However, there are a number of obstacles faced by users, such as language barriers and limited collections.